The Relationship between Internal Forms of Engagement (Cognitive-Affective) and Academic Success across Years of Study - Jaleh Hassaskhah (Issues in Language Teaching, 2013)
Literature has already confirmed that student engagement as an external or multidimensional construct may contribute to the academic success of college students. However, very few studies have tried to examine the contributions the more "internal forms of engagement" (cognitive and affective) might make in this regard, and how the engagement patterns may change over the academic years. To fill the gap, this study was carried out to answer two research questions: (1) what is the relationship between the internal forms of engagement (cognitive-affective) and students’ academic success (represented by Grade Point Average--GPA)? ; (2) How does the pattern of the relationship change across years of study? To do so, a 40-item Cognitive-Affective Engagement Questionnaire (CAEQ) was developed, validated (α=.91), and administered to a sample of 312 undergraduate English major students (222 females and 90 males). The results indicated while cognitive engagement and academic success are positively correlated throughout years of study, the relationship reaches its peak for the affective engagement in the second year and then gradually diminishes. The findings have implications for curriculum and materials developers, as well as the English language teachers who seek programs which can consistently challenge and satisfy students throughout their studies.